Upaya Meningkatkan Kecerdasan Spiritualitas Siswa Dengan Menerapkan Budaya Religius: Literature Review - Annisatul Khoiriyah; Abdul Muhid (Cv. Digital Education Nusantara, 2026)
Writing this literature review paragraph discusses efforts to improve students' spiritual intelligence by implementing religious culture. It is important for students to have spiritual intelligence, because in practice spiritual intelligence will help students in applying positive religious values ​​so that they can behave better. Religious culture is a method of increasing students' spiritual intelligence. Religious culture itself is an attempt to apply the sciences of belief or religion in everyday life. Therefore, in an effort to improve students' spiritual intelligence, religious activities can be carried out in the school environment so that students can make it a habit and apply it continuously. In this study using a literature review approach with qualitative methods. The data used comes from journals and articles. Several previous studies have shown that to increase students' spiritual intelligence, it can be done by applying religious culture.